"From the ground up": Psychoanalytic perspectives on a new system for structuring hospital and clinic care. (24th August 2022) - Lazes, Peter; Rudden, Marie
Abstract: Labor‐Management Partnerships, a new system for structuring hospital care, are based on the recognition that hospitals are complex organizations requiring multiple levels of communication and exchange, and on the premise that front‐line workers are best able to identify and pose solutions to problems in their units and departments. They are structured to form creative problem‐solving teams of managers and staff supported in their work together to improve their hospital within both in individual areas and systemically. Four extensive examples of such teams are provided from two different hospital settings, one public and one not‐for‐profit. Their work is then assessed through the lens of organizational and group psychoanalytic theories.